Bandgap determination and charge separation in AgTiO2 core shell nanoparticle films - Tunc, Ilknur; Bruns, Michael; Gliemann, Hartmut; Grunze, Michael; Kölsch, Patrick (Surface and interface analysis, 2010)
The photocatalytic activity of TiO2 under sunlight irradiation depends on the bandgap energy. Due to the relatively low solar intensity in the UV region (<10%) and the fact that the bandgap of TiO2 is usually greater than 3 eV (below 400 nm), many attempts have been made to shift the bandgap towards lower energies. Here, we investigate the structure, chemical composition, bandgap shift and charge transfer processes of AgTiO2 core-shell nanoparticle thin films by field emission scanning electron microscopy, atomic force microscopy, XPS, and UV-Vis spectroscopy. As a solid support, Au-coated Si wafers and Si surface covered with a native oxide were used and homogenously covered by Ag@TiO2 core-shell nanoparticles with overall film thicknesses of 80-100 nm and size distributions between 8 and 15 nm. The shell thickness of the adsorbed Ag@TiO2 particles was estimated to be 1.5-2.0 nm. The effect of the Ag core on the bandgap of TiO2 and photoinduced charge separation of Ag@TiO2 nanoparticle films was studied by UV-Vis reflectance spectroscopy using the Kubelka-Munk formalism. Films of Ag@TiO2 core-shell nanoparticles revealed a substantially reduced bandgap of 2.75 eV (corresponding to 450 nm), and an electron charge transfer to the Ag core occurring upon UV irradiation on nonconductive surfaces. These features make Ag@TiO2 particulate films a promising candidate for photocatalytic surfaces under sunlight irradiation. Copyright © 2010 John Wiley & Sons, Ltd.
Im Titel ist die Ziffer "2" nach "AgTiO" tiefgestellt
Paper published as part of the ECASIA 2009 special issue
Gesehen am 26.01.2024